Desafios jurídicos das crianças refugiadas indocumentadas e desacompanhadas: a eficácia dos métodos de aferição de suas idades sob a ótica da epistemologia jurídica. - Andrade, Aline Memória de (2021)
Migrations can be voluntary or forced/involuntary. In this last classification, there are refugees, a modality that has special international protection. Of the current number of refugees, more than half are minors, representing a situation of double vulnerability. Even more critical is the situation of unaccompanied refugee children, who characterize another level of vulnerability, lacking family protection. Most of the time, these subjects are also undocumented, invoking the need to assess their ages, given the different and more beneficial treatment of children compared to adults, such as the right to family reunification and special assistance. In Brazil, with the increase in the number of Venezuelan refugees, among whom a large number of unaccompanied children, an analysis of the problem of age assessment methods, the objective of the present study, as well as the investigation of the effectiveness of such methods, is justified. The research begins by addressing preliminary questions about refugee children, such as the fragmentation of the rules that regulate them, leading to insufficient protection. Afterwards, the protection afforded by Europe and Brazil is compared, as well as the parameters for detention of migrant minors established by the European Court of Human Rights and the Inter-American Court of Human Rights, through Advisory Opinion 21/2014. Then, it investigates in which aspects the legal regime of minors is more favorable than that of adults – in the European Union, for example, the child can be exempted from the Dublin System, which provides that the European country responsible for the request asylum is the first one in which the person arrived; thus, in practice, the unaccompanied child can choose the country in which to apply for asylum, which is an enormous advantage of recognizing the age of minority – justifying the problem of age measurement methods, which are not standardized in Europe. In Brazil, there is still little discussion on the topic – which makes the study based on the European Union relevant, where the debates are more advanced –, but there is presumption of legally established minority. Finally, the theme is investigated from the perspective of legal epistemology and it is concluded that there is no scientific certainty in medical methods of age assessment, recommending a holistic or multiprofessional analysis to estimate the age of young migrants, as well as the establishment of a transition category to mitigate the sudden change in the legal regime that affects them when they reach 18 years.